Pancreatic Allograft Thrombosis: Implementation of the CPAT-Grading System in a Retrospective Series of Simultaneous Pancreas-Kidney Transplantation - Petruzzo, Palmina; Ye, Haixia; Sardu, Claudia; Rouvière, Olivier; Buron, Fanny; Crozon-Clauzel, Jullien; Matillon, Xavier; Kanitakis, Jean; Morelon, Emmanuel; Badet, Lionel (Transplant International, 2023)
Pancreatic graft thrombosis (PAT) is a major surgical complication, potentially leading to graft loss. The recently proposed Cambridge Pancreas Allograft Thrombosis (CPAT) grading system provides diagnostic, prognostic and therapeutic recommendations. The aim of the present study was to retrospectively assess computed tomography angiography (CTA) examinations performed routinely in simultaneous pancreas-kidney (SPK) recipients to implement the CPAT grading system and to study its association with the recipients’ outcomes. We retrospectively studied 319 SPK transplant recipients, who underwent a routine CTA within the first 7 postoperative days. The analysis of CTA scans revealed PAT in 215 patients (106 grade 1, 85 grade 2, 24 grade 3), while 104 showed no signs. Demographic data of the patients with and without PAT (thrombosis and non-thrombosis group) were not significantly different, except for the higher number of male donors in the thrombosis group. Pancreatic graft survival was significantly shorter in the thrombosis group. Graft loss due to PAT was significantly associated with grade 2 and 3 thrombosis, while it did not differ between recipients with grade 0 and grade 1 thrombosis. In conclusion, the CPAT grading system was successfully implemented in a large series of SPK transplant recipients and proved applicable in clinical practice.